The need for support and assistance in teenage vulnerable to the non-consensual dissemination of intimate images - Ni Luh Putu Yunianti Suntari; I Dewa Ayu Ketut Surinati; Ni Putu Dessy Parmitha Sari; Ni Made Tariani (Universitas Airlangga, 2026)
The National Commission on Violence Against Women’s Annual Records in 2023 reported sexual violence (2,228 cases), including Non-Consensual Dissemination of Intimate Images (NCII). The “NCII” case in Bali is like an iceberg phenomenon; only a handful have surfaced. The increasingly massive tourism and the development of communication technology are thought to have contributed to the increase in NCII cases in Bali. This research used mixed methods. The first stage used qualitative methods. Results of interviews and FGDs with relevant sources and stakeholders. Obtain data on needs and expected forms of assistance. The second stage quantitatively obtained the effectiveness level of safe spaces for NCII victims. The research target was teenagers aged 10-24 years. This research found that the NCII case still does not receive enough attention in Bali. NCII victims are still reluctant to report their cases, let alone willing to participate in research. Safe spaces are a necessity for vulnerable youth. Peer support helps foster self-confidence and empathy in victims. Help prevent something similar from happening to others. This research proposes that assistance services for NCII victims in Bali focus more on increasing awareness regarding the dangers of NCII, as well as training peer counselors at educational institutions and NGOs.